2019
DOI: 10.1093/scan/nsz104
|View full text |Cite
|
Sign up to set email alerts
|

Let it be: mindful acceptance down-regulates pain and negative emotion

Abstract: Mindfulness training ameliorates clinical and self-report measures of depression and chronic pain, but its use as an emotion regulation strategy—in individuals who do not meditate—remains understudied. As such, whether it (i) down-regulates early affective brain processes or (ii) depends on cognitive control systems remains unclear. We exposed meditation-naïve participants to two kinds of stimuli: negative vs. neutral images and painful vs. warm temperatures. On alternating blocks, we asked participants to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 72 publications
4
52
0
2
Order By: Relevance
“…10,000 h of practice might be a useful criterion to apply for research purposes to define mindfulness practice expertise in the absence of established and reliable objective markers, but it appears to be unhelpful for encouraging individuals to initiate mindfulness practice. Even a simple instruction for mindful emotion regulation of pain experience in meditation-naïve individuals produced the same phenomenological and neural effects as would be expected in experienced mindfulness practitioners (78). A clear distinction should be made when providing a rationale for mindfulness-based approaches between the dose-related effects of mindfulness practice in terms of skills' transfer from state to trait vs. potential benefits gained from mindfulness as a state induced by a single practice session with expected 'spill over' effect, even if short-lived at the early stages of practice development, for dealing with daily pressures and stressors.…”
Section: Mindfulness Provision For Covid-19: Now and The Road Aheadmentioning
confidence: 73%
“…10,000 h of practice might be a useful criterion to apply for research purposes to define mindfulness practice expertise in the absence of established and reliable objective markers, but it appears to be unhelpful for encouraging individuals to initiate mindfulness practice. Even a simple instruction for mindful emotion regulation of pain experience in meditation-naïve individuals produced the same phenomenological and neural effects as would be expected in experienced mindfulness practitioners (78). A clear distinction should be made when providing a rationale for mindfulness-based approaches between the dose-related effects of mindfulness practice in terms of skills' transfer from state to trait vs. potential benefits gained from mindfulness as a state induced by a single practice session with expected 'spill over' effect, even if short-lived at the early stages of practice development, for dealing with daily pressures and stressors.…”
Section: Mindfulness Provision For Covid-19: Now and The Road Aheadmentioning
confidence: 73%
“…In addition, the connectivity between this area and the septal region was found to be enhanced in a mindfulness training group in comparison with a control group during the Ultimate Game (Kirk et al, 2016 ), which suggests that this structure is fundamental in the process of decision-making by switching attention to internal bodily experiences. (Kober et al, 2019 ), using meditation naïve participants, demonstrated that activity in the posterior insula, among other structures, decreases during a meditation in reaction to a heat stimulus. This finding indicates that activity in this area is modulated by mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…, 2009 that did not report behavioural results). Studies with two different experimental conditions ( Kober et al. , 2019 ) or with different groups of participants analysed separately ( Smoski et al.…”
Section: Methodsmentioning
confidence: 99%